Peak phosphorus: Implications for agricultural production, the environment and development - Eric T. Craswell; Holm Tiessen; Paul L. G. Vlek (University of Bonn, Center for Development Research (ZEF), 2010)
Phosphorus is a key element in food production, but is a non-renewable resource. Recent estimates suggest that global production of P fertilizers will peak in 2033 and will be one third of that peak level by the end of the 21st century. Population and income growth will increase demand for food, and especially animal protein, the production of which will accelerate the rundown in P reserves and the consequential rise in fertilizer prices. The global distribution of current P fertilizer use divides countries into the haves which in many cases face severe pollution problems from excess P, and the have-nots in which low input use annually drains soil P reserves. Coping strategies include improvements in the efficiency of fertilizer P manufacture and use, and the recycling of P in liquid and solid wastes. The latter approach offers win-win solutions by reducing the environmental pollution of water in highly populated areas. Future utilisation of scarce P reserves requires policy decisions that take account of equity, productivity, environmental and trade considerations. Biological solutions designed to increase P use efficiency, such as improving crop varieties and mycorrhiza associations, and the use of P accumulating plants as green manures, are also considered.
Keywords: 330; Phosphat; Erschöpfbare Ressourcen; Phosphatdünger; Landwirtschaft; Umweltbelastung; Entwicklung; Welt